FIS students’ performance in Mathematics : comparison between SPM additional Mathematics and first semester exam - Agnes Ayang Anak Kenyang; Wong, Tee Hao (Penerbit Universiti Kebangsaan Malaysia, 2019)
Mathematics teaching and learning encounter quite a big problem, especially at the tertiary level. The main concern always surrounds the students’ achievement in the subject matter. Students’ performance during the first semester of the foundation programme is reflected by the students’ mathematical background prior to the admittance into the university. The study was carried out among 62 students that enrolled in the foundation in science programme in UCTS. Each student is given a pre-test at the beginning of the semester. The pre-test consisted of 10 mathematical questions which students have learnt before. From the results, 61% of these students failed. However, looking into their Sijil Pelajaran Malaysia (SPM) additional mathematics results, the majority of them getting a (24%). These students also took FIS1114 mathematics I during the first semester. At the end of the semester, the result of their FIS1114 mathematics I course was insignificant where the majority of the students failed and obtained pass grade which is below C+. The performance of these three mathematics results was being compared and studied.